2001
DOI: 10.1094/cchem.2001.78.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oat Endoproteinases that Hydrolyze Oat Avenins

Abstract: The prolamin (avenin) patterns of oat (Avena sativa L.) cultivars released in the Czech Republic and in the former Czechoslovak Republic were analysed by acid polyacrylamide gel electrophoresis (A-PAGE). Forty-nine oat (Avena sativa L.) accessions of domestic origin, maintained in the Czech collection of oat genetic resources, were analysed. The evaluated set contained 18 modern and 31 old cultivars. Thirty accessions showed a homogeneous prolamin pattern. The other accessions were heterogeneous with two or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…2A). Alcohol-soluble oat avenins were located in the molecular mass range of 24.5 to 38 kDa, and this was in substantial agreement with the results of Mikola et al (38), who found prolamins of ca. 22 to 33 kDa.…”
Section: Hydrolysis Ofsupporting
confidence: 90%
“…2A). Alcohol-soluble oat avenins were located in the molecular mass range of 24.5 to 38 kDa, and this was in substantial agreement with the results of Mikola et al (38), who found prolamins of ca. 22 to 33 kDa.…”
Section: Hydrolysis Ofsupporting
confidence: 90%
“…The serine and metalloproteinases hydrolysed oat proteins in dissolved form, and when oat proteins were in a bound form cysteine endoproteinase was the main degrading activity. Mikola and Jones (2000b) and Mikola et al (2001) studied the hydrolysis on oat globulins and oat avenins in detail. In the beginning of germination, oat globulins were hydrolysed into intermediate molecular weight peptides.…”
Section: Amino Acid Composition and Protein Degrading Enzymesmentioning
confidence: 99%
“…The cysteine proteinases were able to hydrolyze both oat globulins and avenins, the oat prolamins (Mikola and Jones 2000a;Mikola et al 2001). Mikola concluded that both types of oat storage proteins were hydrolyzed mainly by the cysteine proteinases; therefore it is not so surprising that their endoproteinase complements are quite similar to those of the other species.…”
Section: Oat Endoproteinasesmentioning
confidence: 99%
“…A metalloproteinase from buckwheat (Fagopyrum esculentum Moench) has been purified and studied (Voskoboinikova et al 1989) and some of the oat (Avena sativa L.) and rye (Secale cereale L) proteinases have been partially characterized, but not purified (Mikola and Jones 2000a,b;Mikola et al 2001;Brijs et al 2002). The endoproteinases of most of the other grains have only been studied cursorily, if at all.…”
mentioning
confidence: 99%